2022
DOI: 10.3389/fnbeh.2021.814796
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Socioneuroscience to Research on Coerced and Free Sexual-Affective Desire

Abstract: Neuroscience has well evidenced that the environment and, more specifically, social experience, shapes and transforms the architecture and functioning of the brain and even its genes. However, in order to understand how that happens, which types of social interactions lead to different results in brain and behavior, neurosciences require the social sciences. The social sciences have already made important contributions to neuroscience, among which the behaviorist explanations of human learning are prominent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The main contribution of this article is the evidence that the women participating affirmed that consent was undermined due to coercive discourse (Racionero-Plaza et al, 2022), which impacted the awakening of sexual relationships. Previous research has demonstrated that coercive discourse is widely prevalent in society; it is publicly displayed in the media (Duque et al, 2022;Rodrigues-Mello et al, 2021;Villarejo-Carballido et al, 2022;Willing, 2022), in schools, and in peer interactions (Torras-Gómez et al, 2020;Valls et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The main contribution of this article is the evidence that the women participating affirmed that consent was undermined due to coercive discourse (Racionero-Plaza et al, 2022), which impacted the awakening of sexual relationships. Previous research has demonstrated that coercive discourse is widely prevalent in society; it is publicly displayed in the media (Duque et al, 2022;Rodrigues-Mello et al, 2021;Villarejo-Carballido et al, 2022;Willing, 2022), in schools, and in peer interactions (Torras-Gómez et al, 2020;Valls et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We can state that based on the data collected we can identify that Bond increases his ethical behavior in line with a more inclusive society, however we cannot state -based on the data collected -that he also increases his attractiveness proportionally. The role of the coercive discourse (Racionero-Plaza et al, 2022;Ruiz-Eugenio, Racionero-Plaza, et al, 2020), which fosters attraction to violence (Gómez, MCS -Masculinities and Social Change, 11(2) 117 2015;Valls et al, 2008), towards non-egalitarian masculinities (Castro & Mara, 2014;Flecha et al, 2013;Rodrigues-Mello et al, 2021), in making some people see the last Bond as less attractive would be the subject of future research. How the socialization of people in this coercive discourse mediated to a lesser or greater extent in their perception of a more or less attractive Bond due to having more ethical behaviors remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, findings from the field of socioneuroscience explain how the repeated socialization in the CDD through interactions with media and especially with peers reinforces the internalization of this discourse, that is, of the link between violence and attractiveness (Puigvert Mallart et al, 2019;Racionero-Plaza, Puigvert, et al, 2021;Racionero-Plaza, Ugalde, Merodio, et al, 2020;Racionero-Plaza, Ugalde, Vidu, et al, 2020). The CDD is not only internalized through experience, through engaging in disdainful sexual-affective relationships -especially hookups -, but also, and more so, through the ways in which girls who have had such experience tell their friends about it (Racionero-Plaza, Duque, et al, 2021;Torras-Gómez et al, 2019).…”
Section: State Of the Artmentioning
confidence: 99%